An exploratory investigation of social workers' knowledge and attitudes about autism. Issue 2 (4th March 2018) - Haney, Jolynn L.; Cullen, Jennifer A.
ABSTRACT: Although researchers continue to generate knowledge concerning autism, few have investigated social workers' understanding about this condition. In this exploratory study, we surveyed licensed social workers ( n  = 793) to examine social workers' understanding and attitudes about autism. Overall, we found social workers have accurate knowledge and hold strengths-based attitudes about autism and persons on the autism spectrum. Factors significantly associated with accurate autism knowledge were having special training in autism, having present clinical involvement with autism, and knowing someone on the autism spectrum. Implications for social work practice, education and training, and future research, are discussed.